First Acute Myocardial Infarction (AMI) in the Very Young Versus Older Population: A Clinical and Prognostic Comparison (Journal of Rangpur Medical College, 2026)
Background: South Asians, including Bangladeshis, experience AMI at younger age, yet local comparative data are limited. Objective: This study aimed to compare the very young (≤30 years) versus older (≥50 years) patients presenting with their first AMI. Methods: This cross-sectional comparative study was conducted at Dhaka Medical College and Hospital from July 2022 to December 2023, including 160 first-AMI patients, very young (n=80) and older (n=80), diagnosed by the Fourth Universal Definition (2018). Results: Mean age was 26.4±2.8 vs 61.7±7.4 years; male predominance was higher in the very young (87.5% vs 75.0%, p=0.048). Very young patients had more smoking (57.5% vs 30.0%, p